Play to place physical gameboards as tools for site exploration: P2P – Seri Iskandar - Mohd Nadzamuddin, Ahmad Faiz; Sayed Abul Khair, Sayed Muhammad Aiman; Arman, Muhammad Faris; Mohd Yunus, Muhammad Assyahmizi; Yuserrie, Farid Al Hakeem; Zainal Abidin, Mohammad Nazrin (2025)
Incorporating gamification into architecture education, as exemplified by the Play to Place Physical Gameboards – Seri Iskandar (P2P-SI), has demonstrated significant potential in boosting student engagement and intrinsic motivation while fostering spatial literacy and participatory placemaking principles. The research engaged 99 second-year architectural undergraduates who applied Ludo King-inspired ludic design mechanics to analyze sites, integrating community storytelling elements that reflect local cultural narratives. Grounded in self-determination theory, the methodology emphasized fostering relatedness, competence, and autonomy, aligning gameplay with goals of urban resilience through collaborative problem-solving. Results highlighted that students’ intrinsic motivation was most strongly driven by perceived value/usefulness, effort/importance, and interest/enjoyment. Participants praised the innovative, experiential learning method for making lessons more interactive and memorable, particularly in contextualizing complex urban challenges. Overall feedback indicated that gamification simplifies complex subjects, enhancing accessibility and enjoyment, which in turn improves educational outcomes. The study underscores how strategically crafted extrinsic elements in studio-based learning can cultivate intrinsic motivation effectively, bridging design pedagogy with real-world community-driven priorities.